The price linkages between Malaysian unit trust funds and the stock market index / Zaliza Zulkafli - Zulkafli, Zaliza (2007)
This study examines the price linkages between Malaysian unit trust funds and the five indices from stock market index in Bursa Malaysia which are Industrial Index, Construction Index, Finance Index, Plantation Index and Trading and Services Index. The data can be obtained from Bursa Malaysia and Data Stream. The period for this study covers from year 2000 to year 2006. The dependent variable for this study is unit trust funds while the independent variable is five indices from the stock market index. Multiple Regression analysis is used to identify the price relationship between Malaysian unit trust funds and the five indices from stock market index. The results show that the Construction Index, Service Index and Finance Index have a relationship with the dependent variable, Malaysian unit trust funds. Even though, the Industrial Index and Plantation Index show no relationship with the Malaysian unit trust funds.